Biocompatibility and biomineralization of the experimental nanoparticulate mineral trioxide aggregate (MTA) (Research, Society and Development, 2021)
To investigate the tissue response and the biomineralization ability of the experimental nanoparticulate mineral trioxide aggregate compared to grey MTA and Fillapex MTA. Polyethylene tubes containing materials or empty tubes for control were inserted into the subcutaneous tissues of 30 rats. After 7, 15, 30, 60, and 90 days, the rats were killed and the tubes were removed for analysis using hematoxylin-eosin staining, von Kossa staining, and under polarized light. Inflammation was graded through a score system; the biomineralization ability was recorded as present or absent. The results were statistically analyzed using the Kruskal-Wallis test (p